Hands-on database : an introduction to database design and development - Conger, Steve (Prentice Hall, 2012)
For Introductory Database courses that focus on hands-on experience. Define and develop a database through a scenario approach. Hands-On Database uses a scenario-based approach that shows students how to build a database by providing them with the context of a running case throughout each step of the process